2018
DOI: 10.1371/journal.pone.0202973
|View full text |Cite|
|
Sign up to set email alerts
|

Light correlated color temperature and task switching performance in preschool-age children: Preliminary insights

Abstract: Data from a growing number of experimental studies show that exposure to higher correlated color temperature (CCT) ambient light, containing more blue light, can positively impact alertness and cognitive performance in older children and adults. To date, few if any studies have examined whether light exposure influences cognitive task performance in preschool-age children, who are in the midst of rapid developmental changes in attention and executive function skills. In this study, healthy children aged 4.5–5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Six methods for data collection were identified from the studies on performance/productivity. Direct measurement of performance was used in 23 studies [30,[32][33][34][35]38,[48][49][50]55,57,64,66,68,71,74,87,91,94,[98][99][100]103] through a wide range of standardized tests, which covered mental functions as attention (sustained attention, attention to detail, vigilance tasks, reaction time) and cognition (logic, vocabulary, reading comprehension, problem solving, memory, cognitive speed, cognitive flexibility, creativity). Academic performance was analyzed in two studies using students' grades [58,104].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Six methods for data collection were identified from the studies on performance/productivity. Direct measurement of performance was used in 23 studies [30,[32][33][34][35]38,[48][49][50]55,57,64,66,68,71,74,87,91,94,[98][99][100]103] through a wide range of standardized tests, which covered mental functions as attention (sustained attention, attention to detail, vigilance tasks, reaction time) and cognition (logic, vocabulary, reading comprehension, problem solving, memory, cognitive speed, cognitive flexibility, creativity). Academic performance was analyzed in two studies using students' grades [58,104].…”
Section: Discussionmentioning
confidence: 99%
“…Only 17 studies reported the use of any shading device. Twenty-nine studies focused on artificial lighting, did not have shading devices due to windowless experimental settings [30,32,35,37,40,43,45,[47][48][49]54,55, 59,63,64,67,68,70,72,74,75,78,80,82,84,86,88,96,97]. When considered, shading devices were mostly internal.…”
Section: View To the Outside Type Of Lamps And Shading Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, further review showed a contradiction between the impacts of lighting under controlled and field experiments, indicating that lighting infield experiments, which test in conditions much closer to everyday life, could be more precise in predicting the effect of lighting on the learning potentials of students in real-life situations [3]. Hartstein et al, however, examined the light exposure influences on cognitive task performance in 38 preschool children aged 4.5-5.5 by dividing them into two groups, the control (n = 18) and experimental group (n = 20), and exposing them to two different tasks aimed at measuring their sustained attention and task switching abilities, under varying lightemitting diode (LED) lighting condition of 3500K or 5000K [2]. The control group engaged the two-study task twice under the 3500K lighting conditions, while the experimental group had the two-study task under the 3500K lighting conditions as a baseline assessment, and after that, the 5000K lighting conditions.…”
Section: Impact Of Lighting On the Learning Environment: Using Academic Performance As A Test Parametermentioning
confidence: 99%
“…There remains a need for focused, systematic research into the influence of the physical aspects of students' learning environment, by measuring various factors such as air quality, noise levels/music, plants, and lighting, reported to influence childrens' performance and wellbeing [1]. Lighting was reported to be an important factor that affects student learning and growth in the classroom environment [2], [3], so this review will present the collective findings on the impact of daylight on the learning environment, plus how to enhance lighting to influence the behavior and cognitive learning capabilities of children.…”
Section: Introductionmentioning
confidence: 99%